2014
DOI: 10.1128/aac.01445-13
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Compounds Blocking the Proliferation of Toxoplasma gondii and Plasmodium falciparum in a Chemical Space Based on Piperidinyl-Benzimidazolone Analogs

Abstract: A piperidinyl-benzimidazolone scaffold has been found in the structure of different inhibitors of membrane glycerolipid metabolism, acting on enzymes manipulating diacylglycerol and phosphatidic acid. Screening a focus library of piperidinyl-benzimidazolone analogs might therefore identify compounds acting against infectious parasites. We first evaluated the in vitro effects of (S)-2-(dibenzylamino)-3-phenylpropyl 4-(1,2-dihydro-2-oxobenzo[d]imidazol-3-yl)piperidine-1-carboxylate (compound 1) on Toxoplasma gon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Recently, it was found that certain parasites might also utilize pathways downstream of PLDs. This was illustrated by in vitro experiments showing that PLD inhibitors such as VU0285655 can block the proliferation of Plasmodium falciparum (one of the causal agents of malaria) and that of Toxoplasma gondii (which causes toxoplasmosis) 64 .…”
Section: Pld Enzymes In Infectious Diseasesmentioning
confidence: 99%
“…Recently, it was found that certain parasites might also utilize pathways downstream of PLDs. This was illustrated by in vitro experiments showing that PLD inhibitors such as VU0285655 can block the proliferation of Plasmodium falciparum (one of the causal agents of malaria) and that of Toxoplasma gondii (which causes toxoplasmosis) 64 .…”
Section: Pld Enzymes In Infectious Diseasesmentioning
confidence: 99%
“…En modélisant la structure tridimensionnelle de la galvestine-1 et du DAG, il a en effet été possible de superposer la partie pipéridinyl-benzimidazolone avec la zone proche du squelette glycérol du DAG [9]. En considérant, d'une part, l'importance vitale du métabolisme des glycérolipides pour les eucaryotes, et, parmi eux, des eucaryotes pathogènes de l'homme et, d'autre part, la possibilité de faire varier la spécificité de cible des pipéridinyl-benzimidazolone, une chimiothèque d'analogues, contenant des motifs structuraux communs à la galvestine-1, à l'halopémide et à VU0285655, a été criblée pour rechercher des agent anti-infectieux inhibant la prolifération de Plasmodium falciparum et de Toxoplasma gondii [22]. Ces parasites appartiennent au groupe des Apicomplexes, proches dans l'évolution des algues [23], responsables respectivement du paludisme et de la toxoplasmose.…”
Section: Les Phospholipases D Humainesunclassified
“…The vestigial origin of the apicoplast has paved the way for innovative antimalarial drugs that can be described as herbicidal therapies. Among the biocides targeting the apicoplast, triclosan showed antiparasitic activity against Plasmodium through the fatty acid biosynthesis pathway inhibition located in the apicoplast [ 19 ], although it was off-target and not active in vivo [ 20 ].…”
Section: Introductionmentioning
confidence: 99%